Teaching Residents to Teach: Do Program Directors and Trainees Agree on Format and Content? - Lacasse, Miriam; Routhier, Gaétane; LeBlanc, Pierre; Théorêt, Johanne; Glenn, Joan; Ratnapalan, Savithiri (Canadian Medical Education Journal, 2010)
Background: Despite the important number of teaching-skills programs described in the literature, previous needs assessment of such curricula have examined primarily residents’ perceived learning needs in this field. The purpose of this study was to identify the optimal content and format of a resident teaching-skills training curriculum and compare the perspective of medical students (MS), residents and residency program directors (PD). Methods: This needs assessment was an observational study with a cross-sectional design. Online or printed questionnaires were used to assess the preferred format and content for this curriculum among MS, residents from most postgraduate medical training programs, and PD from Faculté de médecine de l’Université Laval. Results: The questionnaires were completed by 26 PD (response rate 72.2%), 146 residents (response rate 21.9%) and 154 MS (response rate 15.7%). Among the list of potential subjects that could be included in the curriculum, Learning styles, Working with students in difficulty and Self-directed learning were scored high by both residents and PD. MS favored Learning styles, Teaching in the ambulatory care setting, Teaching health promotion and prevention, Teaching with time constraints and Direct supervision strategies. PD also favored Teaching conflict management and Teaching professionalism, however these were both among the residents’ lower scores. The preferred formats were One half-day, One day and Online learning for PD and One day, Two consecutive days and A few one-day sessions over several months for residents. Conclusion: The PD and MS perception of the optimal format and content for residents’ teaching-skills training showed some discrepancies when compared with residents’ preferences. Since PD are largely involved in curriculum development for their respective specialties and since MS are also well positioned to assess residents’ teaching performance, we suggest that PD, residents and MS should all be consulted locally before organizing any intervention for teaching curricula.